2015
DOI: 10.1038/srep11682
|View full text |Cite
|
Sign up to set email alerts
|

Widespread tsunami-like waves of 23-27 June in the Mediterranean and Black Seas generated by high-altitude atmospheric forcing

Abstract: A series of tsunami-like waves of non-seismic origin struck several southern European countries during the period of 23 to 27 June 2014. The event caused considerable damage from Spain to Ukraine. Here, we show that these waves were long-period ocean oscillations known as meteorological tsunamis which are generated by intense small-scale air pressure disturbances. An unique atmospheric synoptic pattern was tracked propagating eastward over the Mediterranean and the Black seas in synchrony with onset times of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 26 publications
6
68
0
Order By: Relevance
“…2), where a decrease in mid-tropospheric winds is not followed by a decrease in the NSLOTT variance. The importance of mid-tropospheric winds in generating NSLOTT events has been recognized in a number of studies131819, which show that 500-hPa winds (at the level of the mid-tropospheric jet) are exceptionally strong during NSLOTT events.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2), where a decrease in mid-tropospheric winds is not followed by a decrease in the NSLOTT variance. The importance of mid-tropospheric winds in generating NSLOTT events has been recognized in a number of studies131819, which show that 500-hPa winds (at the level of the mid-tropospheric jet) are exceptionally strong during NSLOTT events.…”
mentioning
confidence: 99%
“…These patterns have so far been recognized in a few regional studies18192021. To check for the existence of globally dominant NSLOTT synoptic patterns, we extracted the most extreme NSLOTT episodes (in terms of their maximum range) from a number of representative stations with multi-annual high-quality sea level series and related them to the ECMWF (European Centre for Middle-range Weather Forecasts) ERA-Interim reanalysis fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ŠEPIĆ et al (2015) showed that the passage of pronounced atmospheric disturbances is roughly concurrent with the onset of strong sea level oscillations. In addition they reported that although the linkages between enhanced sea level oscillations and intensified atmospheric disturbances are highly non-linear, the time series are clearly indicative of a cause and effect relationship.…”
Section: Resultsmentioning
confidence: 99%
“…These fronts propagate above the sea at a resonant speed, allowing efficient energy transfer between the atmospheric disturbance and the sea wave that it generates. ŠEPIĆ et al (2015) studied atmosphere induced long ocean waves in the Mediterranean and Black Seas generated by high-altitude atmospheric forcing by using spectral wavelet analysis.…”
Section: Resultsmentioning
confidence: 99%